1984
DOI: 10.1902/jop.1984.55.10.608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorhexidine on the Structure and Permeability of Hamster Cheek Pouch Mucosa

Abstract: This study examined the effects of chlorhexidine (CHD) on the clinical appearance, morphology, and in vitro permeability of hamster cheek pouch mucosa. The cheek pouches were treated daily for 3 weeks with topical applications of saline, 0.2% CHD, or 2.0% CHD. Treatment with 2.0% CHD resulted in the formation of discrete white lesions in every animal in the group, whereas no changes were identified in any animal treated with 0.2% CHD or saline. Upon microscopic examination it was determined that treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Using hamster check pouch mucosa, it has been reported that intermittent applications (5 min daily for 3 weeks) of 0.2% CH produced no effeet, whereas 2.0% CH eaused epithelial hyperplasia and hyperkeratosis similar to that which we observed with continuous exposure to 0.2% CH for 3 days (13). It was also found that, in specimens exhibiting epithelial hyperkeratosis, there was an increase in the permeability barrier to tritiated water and horseradish peroxidase (13).…”
Section: Discussionsupporting
confidence: 82%
“…Using hamster check pouch mucosa, it has been reported that intermittent applications (5 min daily for 3 weeks) of 0.2% CH produced no effeet, whereas 2.0% CH eaused epithelial hyperplasia and hyperkeratosis similar to that which we observed with continuous exposure to 0.2% CH for 3 days (13). It was also found that, in specimens exhibiting epithelial hyperkeratosis, there was an increase in the permeability barrier to tritiated water and horseradish peroxidase (13).…”
Section: Discussionsupporting
confidence: 82%
“…An interesting exception to this statement has recently been provided by the observation that the antimicrobial agent, ehlorhexidine. is capable of inducing a hyperplastic cheek pouch epithelium that does show re-dueed permeability (14). This effeet may refleet the strong binding of the divalent ehlorhexidine moleeule to eharged groups on the epithelial surfaee.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in an animal study, topical application of CHX was reported to result in its penetration through the epithelial barrier, causing tissue damage [10]. Withrow et al [32] reported CHX to be toxic for mouse lymphoma cells.…”
Section: Introductionmentioning
confidence: 99%